INTEGRATING SHORT STORIES IN THE EFL CLASSROOM FOR DEVELOPING LEARNERS’ COMMUNICATIVE COMPETENCE: INTEGRATING SHORT STORIES IN THE EFL CLASSROOM FOR DEVELOPING LEARNERS’ COMMUNICATIVE COMPETENCE - Bisenova, Aliya; U. Orazbaeva, U. Orazbaeva (Журнал иностранных языков и лингвистики, 2025)
It is well known that the English language has become a global language. In some countries it has been used as mother tongue and in other countries it is learnt as a second language. In that way, English language is the only medium of communication/ instruction for the speakers of other languages. Louis H. Gray defines that “language may be said to be any means of expressing emotional or mental concepts by any living being or beings whatsoever and of communicating them to, or receiving them from, other living beings